Rethinking race : Franz Boas and his contemporaries - Williams, Vernon J. (Lexington, Ky. : University Press of Kentucky, 1996)
In this thought-provoking reexamination of the history of ""racial science"" Vernon J. Williams argues that all current theories of race and race relations can be understood as extensions of or reactions to the theories formulated during the first half of the twentieth century. Williams explores these theories in a carefully crafted analysis of Franz Boas and his influence upon his contemporaries, especially W.E.B. DuBois, Booker T. Washington, George W. Ellis.
Franz Uri Boas' paradox -- Boas and the African American intelligentsia -- The myths of Africa in the writings of Booker T. Washington -- W.E.B. Du Bois, George W. Ellis, and the reconstruction of the image of Africa -- Robert Ezra Park and race and class relations.
Includes bibliographical references (pages 127-133) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Boas, Franz, -- 1858-1942.; Boas, Franz, -- 1858-1942.; Boas, Franz, -- 1858-1942; Boas, Franz -- 1858-1942; Umschulungswerkstätten für Siedler und Auswanderer; Boas, Franz, -- 1858-1942.; Boas, Franz; Anthropologists -- United States -- Biography; Anthropologists -- United States -- Attitudes; Physical anthropology -- United States -- History; Racism -- United States -- History; African Americans -- Public opinion; Public opinion -- United States; United States -- Race relations; Anti-racism -- United States -- History; Anthropologues -- États-Unis -- Biographies; Anthropologues -- États-Unis -- Attitudes; Anthropologie physique -- États-Unis -- Histoire; Racisme -- États-Unis -- Histoire; Noirs américains -- Opinion publique; Opinion publique -- États-Unis.; Antiracisme -- États-Unis -- Histoire; États-Unis -- Relations raciales; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; Anti-racism; African Americans -- Public opinion; Anthropologists; Anthropologists -- Attitudes; Physical anthropology; Public opinion; Race relations; Racism; United States; Rassentheorieën.; Race Relations -- history; Anthropology, Physical -- history; Public opinion -- United States; Schwarze; Geschichte; Humanbiologie; Rassentheorie; Schwärze; USA; Racism; Anthropology -- United States; Anthropologists -- United States -- Attitudes; Physical anthropology -- United States -- History; Racism -- United States -- History; African Americans; United States -- Race relations; Society; African Americans -- Public opinion; Anthropologists -- Attitudes -- United States; Anthropologists -- Biography -- United States; Boas, Franz; Physical anthropology -- History -- United States; Public opinion -- United States; Racism -- History -- United States; United States -- Race relations; Biographies